Study of the Impact of Unsteady Squeezing Magnetohydrodynamics Copper-Water with Injection-Suction on Nanofluid Flow Between Two Parallel Plates in Porous Medium - Jasim, Abeer Majeed (Iraqi Journal of Science, 2022)
In this article, the existence of thermal radiation with Copper- water nanofluid, the effect of heat transfer in unsteady magnetohydrodynamics (MHD) squeezing and suction-injection on the flow between parallel plates( porous medium) are studied. Rosseland approximation and the radiation of heat flux are used to depict the energy equation. The set of ordinary differential equations with boundary conditions are analytically resolved by applying a new approach method (NAM). The influences of thermal field and physical parameters on dimensionless flow field have been displayed in tabular and graphs form. The presented results show that the heat transfer coefficient is reduced by the thermal radiation coefficient increases and the absolute values of the skin friction coefficients are enhanced with the magnetic amplification parameter. Regularly, the present outcomes discern that the parameters of the injection-suction coefficient are both the temperature and velocity profiles decline.